1999
DOI: 10.1177/009286159903300115
|View full text |Cite
|
Sign up to set email alerts
|

Global Two-Group Multiple Endpoint Adjustment Methods Applied to Clinical Trials

Abstract: Ojien, clinical trial results are reported and used for claiming a treatment effect without adjusting for the multiplicity arising from the presence of multiple endpoints. It is well recognized that this practice is likely to inflate the type I error rate unless the endpoints are highly correlated. To control such an inflation of the type 1 error rate, two approaches, both appropriate on their own grounds, are in use. One is the 'global' approach which aims at demonstrating overall treatment effect and conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…As a preliminary, we used a global approach and analyzed treatment effects by multivariate analysis of variance (MANOVA), based on mean change in symptom score 21 . Dependent variables were combined in five symptom categories (See Table 3) with the independent categorical variable in each of the five models being treatment status.…”
Section: Discussionmentioning
confidence: 99%
“…As a preliminary, we used a global approach and analyzed treatment effects by multivariate analysis of variance (MANOVA), based on mean change in symptom score 21 . Dependent variables were combined in five symptom categories (See Table 3) with the independent categorical variable in each of the five models being treatment status.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, total sample size conditions ranged from N = 20 to N = 100 (Sankoh et al, 1999;Mudholkar et al, 2001). Lix and Fouladi (2007) demonstrated that Type I error and power rates of the composite step-down test are sensitive to the ratio N=m.…”
Section: Methodsmentioning
confidence: 99%
“…Power to detect departures from the null hypothesis is influenced by both the magnitude and pattern of correlation among the outcome measures (Sankoh et al, 1999). Three correlation matrices were investigated: ρ j = Q, ρ j = R, and ρ j = T (j = 1, 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in a highly liberal ALR test if one uses the null distribution derived by Tang et al which assumes a known covariance matrix; see Reitmeir and Wassmer (1996) and Sankoh et al (1999 The outline of the paper is as follows. In Section 2 we set the notation and review the ALR test for the two sample problem in the known common covariance matrix (homoscedastic)…”
Section: Introductionmentioning
confidence: 99%